External finance constraints and the intertemporal pattern of intermittent investment - Whited, Toni M. (Journal of Financial Economics, 2006)
Do external finance constraints affect the timing of large investment projects? Simulations of a model with fixed capital-stock adjustment costs establish the hypothesis that external finance constraints lower a firm's investment hazard: the probability of undertaking a large project today as a function of the time since the last project. Hazard model estimation that controls for productivity and adjustment costs supports this hypothesis. Small firms that distribute cash to shareholders have higher hazards than small firms that do not; very small firms have lower hazards than small firms; small stand-alone firms have significantly lower hazards than small segments of conglomerates.